Hydroelectric Power : A Guide for Developers and Investors - International Finance Corporation (Washington, DC, 2015)
Worldwide, hydropower is a crucial power supply option for several reasons. First, it is a renewable energy resource that can contribute to sustainable development by generating local, typically inexpensive power. Second, hydropower reduces reliance on imported fuels that carry the risks of price volatility, supply uncertainty and foreign currency requirements. Third, hydro systems can offer multiple co-benefits including water storage for drinking and irrigation, drought-preparedness, flood control protection, aquaculture and recreational opportunities, among others. Finally, hydro can allow more renewables, especially wind and solar, to be added to the system by providing rapid-response power when intermittent sources are off-line, and pumped energy storage when such sources are generating excess power. For more publications on IFC Sustainability please visit www.ifc.org/sustainabilitypublications.